Levels of phospholipids and triacylglycerol-containing omega 3 fatty acids in myocardial tissue of patients with myocardial infarction: analyzed by a lipidomics profiling method. (25th November 2020) - Shiozawa, T; Shimada, K; Lee-Okada, H; Kadoguchi, T; Aikawa, T; Hayashi, H; Miyazaki, T; Matsushita, S; Suwa, S; Yokomizo, T; Amano, A; Nakazato, Y; et al.
Abstract: Objective: According to population-based studies, low omega 3 fatty acid (omega3FA) intake and high levels of serum triacylglycerol (TAG) are associated with cardiovascular diseases. Recent advances in mass spectrometry allow molecular lipid (lipidomics) profiling, which may enhance cardiovascular risk prediction. In this study, we assessed the levels of omega3FA-containing phospholipids (PL) and TAG in myocardial tissues of patients with and without myocardial infarction (MI) using a lipidomics profiling method. Methods: We performed lipidomics profiling of human left atrial appendage (LAA) tissue of 29 consecutive patients receiving off-pump coronary bypass surgery with standard LAA resection. The patients were divided into the MI group (n=7) and an age- and gender-matched non-MI group (n=7). Results: Lipidomics profiling revealed that the MI group tended to have low levels of phosphatidylcholines (PC), phosphatidylethanolamine (PE), lysophosphatidylethanolamine (LPE), and plasmalogen, and high levels of TAG species. Individual molecular species containing omega3FA, such as PC (18:0/20:5; 3, 200±1, 200 vs. 4, 500±910 pmol/g tissue, p=0.04) and plasmalogen (18:1/20:5; 57, 000±21, 000 vs. 91, 000±28, 000 pmol/g tissue, p=0.02), were significantly lower in the MI group than in the non-MI group. Conclusions: To our knowledge, this is the first study to determine the levels of omega3FA-containing PL and TAG in myocardial tissue using lipidomics profiling. We discovered that lower levels of omega3FA-containing PL and higher levels of TAG existed in myocardial tissues of patients with MI than in those of patients without MI. Accordingly, the lipidomics profiling method for human myocardial tissue may be useful for developing therapy targets for cardiovascular diseases. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): MEXT/JSPS KAKENHI Grant